DEVELOPMENT OF WRITTEN SPEECH IN MEDICAL STUDENTS IN THE RUSSIAN LANGUAGE CLASSES IN A MEDICAL UNIVERSITY - Ахмедова Уктамхон (European Journal of Interdisciplinary Research and Development, 2023)
This article provides information that students of medical universities in the learning process master several foreign languages, especially one of the greatest languages - Russian. Students of medical universities should pay special attention not only to oral speech, but also to the development of written speech. They reflect their professional activities in writing, so they must write correctly, perform various types of written work that activate mental activity and improve the literacy of medical students.